Comparison Between Topographic-Based and Manifest-Based Astigmatism Corrections in the Second (Visumax 800)-Generation Keratorefractive Lenticule Extraction Surgery: A Real-World Study - Chia-Yi Lee; Hung-Chi Chen; Shun-Fa Yang; Yi-Jen Hsueh; Chin-Te Huang; Jing-Yang Huang; Ie-Bin Lian; Chao-Kai Chang (Diagnostics)
Objectives: To evaluate the effectiveness of astigmatism correction between topographic- and manifest-based methods in individuals who underwent second-generation keratorefractive lenticule extraction (KLEx) surgery. Methods: This study was conducted with participants who underwent second-generation KLEx surgery. After exclusion, there were 46 and 43 participants in the manifest and topographic groups, respectively. The main outcomes were postoperative uncorrected distance visual acuity (UDVA), spherical equivalent (SE), and residual astigmatism. The independent T-test and generalized estimate equation were used to investigate differences between the two groups. Results: Three months postoperatively, UDVA was 0.02 ± 0.04 in the manifest group and 0.00 ± 0.06 in the topographic group which also revealed no significant difference (p = 0.155). Also, the SE value in the two groups three months postoperatively was statistically similar (−0.57 ± 0.48D versus −0.63 ± 0.62D, p = 0.574). The final residual astigmatism was −0.26 ± 0.27 in the topographic group which was significantly lower than the −0.51 ± 0.40 in the manifest group (p < 0.001). Moreover, the amplitude of astigmatism change was significantly lower in the topographic group (p = 0.002). In the subgroup analysis, UDVA and residual astigmatism were significantly better in the topographic group than in the manifest group (both p < 0.05). Conclusions: The topographic-based method represents a better astigmatism correction than the manifest-based method in second-generation KLEx surgery, especially in the low astigmatism population.